Correlating mechanical properties of sinter phases with their chemistry and its effect on sinter quality. (7th February 2017) - Sinha, M.; Nistala, S. H.; Chandra, S.; Mankhand, T. R.; Ghose, A. K.
Abstract : In this study, pot sinter tests were carried out to study the sintering properties of iron ores of different alumina (2–4–6%) level. It was observed that the 6% alumina level ores have a higher RDI values and decreased tumbler index (TI) compared to its other two counterparts. It was observed that an increase in composite fracture toughness (CFT) of sinter improves the Tumbler as well as RDI of the sinter. Beyond 4 CFT there is remarkable improvement in TI, RDI and RI values. The mechanical strength parameters of sinter phases were further correlated and analysed with respect to the chemistry of sinter and mineralogy of sinter phases. There is strong evidence which suggests that the Al2 O3 deteriorates the strength of the phases by making them hard and thus generating cracks in them. Unlike alumina, CaO and SiO2 tend to stabilise and improve the strength of the phase.